An evaluation of the governance structure of marine services in South Africa's ports system - Sphiwe Eugene Mthembu; Mihalis Chasomeris (Journal of Shipping and Trade (JST), 2023)
Port governance structures are a vital factor impacting port investments, efficiencies, effectiveness and productivity. An important determining factor is the port management and whether it is centralized under the national government as a State-Owned Enterprise (SOE), decentralized to the municipal level, or alternatively privatized. Reforms in port management indicate that ports either subscribe to a public service port, tool port, landlord port or private port approach. Several inefficiencies exist in the governance, pricing and performance of marine services in South Africa. This study aims to evaluate the governance structure of marine services in South Africa's ports. The research methodology included observations, a focus group with six participants and semi-structured interviews with twenty participants that included port managers, harbour masters, port experts, port agents, terminal operators, and cargo owners. The main findings confirmed the need for the participation of private service providers in the provision of marine services in South Africa's ports and additional regulations on marine services to advance investment, performance and protection of port users. Although there is a need for private sector participation in the provision of marine services in South Africa's ports, participation should enhance the country's economic and developmental agenda, including job creation, investment in infrastructure, improved service provision and transforming the ports system.
Keywords: 650; Investment; Marine services; Port governance; Port pricing; Port productivity; Privatisation